227k views
3 votes
9 * -2 n + 3 equals -27

2 Answers

6 votes

Answer:

that would be x= 3

Explanation:

If you were to times -2n and 3 that would make -18 + 27.

You then subtract 27 from -27 making it -54. You then divide -18 from -54 making it into a positive 3. So x = 3

User Najeebullah Shah
by
5.5k points
2 votes

Answer:

n=5/3

Explanation:

Step 1: Simplify both sides of the equation.

−18n+3=−27

Step 2: Subtract 3 from both sides.

−18n+3−3=−27−3

−18n=−30

Step 3: Divide both sides by -18.

−18n−18=−30−18

n=53

User Codoscope
by
5.1k points